Epistemología de la historia de vida en la investigación cualitativa - Vidanovic Geremich, Andrea (2018)
The process of knowing from the field of science has varied in its ways of approaching phenomena from epistemology, establishing in time various methods dominated by the positivist paradigm and the postpositivist paradigm, the latter giving value to the subject and their interaction with others ; From this representation, we think of a dialectic between the knower and the known subject. The purpose of the present study is to deepen the epistemology of life history in qualitative research; For this purpose, a documentary review was carried out and several authors who have contributed significantly to the biographical approach were considered. The results are specified: the life history is a method derived from the biographical approach, responds to the qualitative orientation; this method focuses on the totality of life of a subject represented in a story, giving reason to the internal and social world of the historian. Within this framework, life history requires a methodological process that is detailed in the following steps: insertion and selection of subjects, production, collection and transcription of life history, as well as its interpretation through hermeneutics to identify the senses and emerging meanings.